2014
DOI: 10.1080/17521882.2014.924543
|View full text |Cite
|
Sign up to set email alerts
|

Chief Executive Officers' perceived value of coaching: individual and organisational influences

Abstract: Although coaching is widely being used as a means for leadership development, very little is known regarding CEOs' perceived value of coaching and those factors that influence these perceptions. Using 583 complete surveys from a national US survey of hospitals, this article examines the relationship of organisational and individual characteristics to the value CEOs have of coaching. National survey data of hospital CEOs in the USA were used in this research. Analyses included means, correlations, a Duncan-Wall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Hence, planning an effective action plan to achieve performance and developmental goal of subordinates as well as supporting subordinates to carry out their development plans to increase organizational performance are equally important competencies to have an impact on coaching effectiveness. The ability to ask questions that reveal the information needed for maximum benefit to the coaching relationship and the coachee along with using ideas of coachees and shared decision-making are also important competencies in influencing coaching effectiveness (Walston, 2014). However, this finding contradicts Wheeler (2011), as he found that managerial coaching is less willing to challenge and confront.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, planning an effective action plan to achieve performance and developmental goal of subordinates as well as supporting subordinates to carry out their development plans to increase organizational performance are equally important competencies to have an impact on coaching effectiveness. The ability to ask questions that reveal the information needed for maximum benefit to the coaching relationship and the coachee along with using ideas of coachees and shared decision-making are also important competencies in influencing coaching effectiveness (Walston, 2014). However, this finding contradicts Wheeler (2011), as he found that managerial coaching is less willing to challenge and confront.…”
Section: Discussionmentioning
confidence: 99%
“…Going beyond coachee motivation and traits, there might be other environmental factors influencing executives' perceptions that do not directly depend on either the coach or the coachee. We believe that there is promising research opportunity to find common ground in this research direction, which to date has focused more on the organizational factors of coaching (Lewis and Fagenson, 1995;Wade, 2004;Walston, 2014).…”
Section: Theoretical Constructs Moderatorsmentioning
confidence: 99%
“…The rapid growth of coaching practice has outpaced research (Bennett, 2006), and executive coaches tend to use frameworks and models that reflect popular practices rather than being empirical evidence based (Lowman, 2005). There is evidence that the perceived value [1] of coaching is contingent on organizational and individual factors (Lewis and Fagenson, 1995;Wade, 2004;Walston, 2014), but the existing literature has less evidence on how different elements from the coach-coachee setting are related with each other and can affect it. Therefore, this study has two goals: first, explore how the coach-coachee setting [2] can affect the perceived value from the coaching received and second, integrate our findings with the existing literature in a comprehensive theoretical framework.…”
Section: Introductionmentioning
confidence: 99%
“…Among the 12 roles of medical teachers, four of these roles are in favour of oneto-one encounters, such as teaching role modeling, facilitation of learning, mentoring and assessment (8). Teachers can be trained on these roles through peer coaching (coteaching); a model of supervision by peers aiming at improvement of competency in teaching, facilitation, reflection as well as coaching of students (11,12).…”
Section: Introductionmentioning
confidence: 99%